TAX AVOIDANCE: PROFITABILITAS, LIKUIDITAS DAN FINANCIAL DISTRESS PERAN UKURAN PERUSAHAAN SEBAGAI MODERASI - Nurfarida Nurfarida; Sri Andriani (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
The purpose of this study is to empirically test the effect of profitability, liquidity and financial distress on tax avoidance by adding company size as a moderating variable in energy sector companies listed on the IDX during the period 2021-2023. In this study, the Random Effect Model (REM) is the selected testing model using the Eviews program. This study uses a quantitative approach. The sample selection method uses purposive sampling, which produces 40 companies as samples. The results of the study show that profitability and liquidity have no effect on tax avoidance, while financial distress has an effect on tax avoidance. In addition, company size is unable to moderate the effect of profitability and liquidity on tax avoidance, while company size is able to moderate the effect of financial distress on tax avoidance.